2017
DOI: 10.1177/0969733016687162
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and consent: Knowledge and practice of legal and healthcare standards

Abstract: The legal context of decision-making capacity and consent to treatment appears complex for healthcare practitioners. Professional, ethical and legal standards of care in this context can benefit from structured education programmes and supportive governance processes. An understanding of why 'duty of care' is being used as a framework within the context of impaired decision-making capacity is warranted, alongside a review of the context of Duty of Care within health policy, guidance and faculty teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Poor knowledge of regulation may lead healthcare practitioners to illegally authorize restrictive practice (Lamont et al . 2016, 2019).…”
Section: Issues For Concernmentioning
confidence: 99%
“…Poor knowledge of regulation may lead healthcare practitioners to illegally authorize restrictive practice (Lamont et al . 2016, 2019).…”
Section: Issues For Concernmentioning
confidence: 99%
“…[16] In Australia, a study done by Scott Lamont et al also concluded that there is prevalence of confusion amongst the healthcare professionals regarding the legalities of decision-making capacity and consent to treatment and that structured educational tools are the need of the hour. [17].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Assessment of capacity and decision-making should be core skill of all clinicians (Barry & Docherty, 2018). While occupational therapists have been included in research examining DMC assessments in the UK (Jayes et al, 2017;Lamont et al, 2017), limited research exploring the role of occupational therapy has been conducted to date. Moye and Marson (2007) summarised the scope and practice of judicial review of various civil capacities relevant to older adults.…”
Section: Role Of Occupational Therapymentioning
confidence: 99%
“…Following a review of literature examining health and social care professionals practice in the area of decision-making capacity, a questionnaire was developed. The survey questions were informed by surveys used in previous studies that had investigated the assessment of decision-making capacity by lawyers (Helmes, Lewis, & Allan, 2004), neuropsychologists (Mullaly et al, 2007), speech-language pathologists (Aldous, Tolmie, Worrall, & Ferguson, 2014;Jayes et al, 2017;McCormick, Bose, & Marinis, 2017) and non-specified health-care practitioners (Lamont et al, 2017). These items were contextualised to fit within occupational therapy practice and addressed the domains of DMC assessment defined by Moye and Marson (2007…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation